Interlocking Nailing Versus Interlocking Plating in Intra-articular Calcaneal Fractures: A Biomechanical Study. (August 2016) - Reinhardt, Sophia; Martin, Heiner; Ulmar, Benjamin; Döbele, Stefan; Zwipp, Hans; Rammelt, Stefan; Richter, Martinus; Pompach, Martin; Mittlmeier, Thomas
Background: Open reduction and internal fixation with a plate is deemed to represent the gold standard of surgical treatment for displaced intra-articular calcaneal fractures. Standard plate fixation is usually placed through an extended lateral approach with high risk for wound complications. Minimally invasive techniques might avoid wound complications but provide limited construct stability. Therefore, 2 different types of locking nails were developed to allow for minimally invasive technique with sufficient stability. The aim of this study was to quantify primary stability of minimally invasive calcaneal interlocking nail systems in comparison to a variable-angle interlocking plate. Material and Methods: After quantitative CT analysis, a standardized Sanders type IIB fracture model was created in 21 fresh-frozen cadavers. For osteosynthesis, 2 different interlocking nail systems (C-Nail; Medin, Nov. Město n. Moravě, Czech Republic; Calcanail; FH Orthopedics SAS; Heimsbrunn, France) as well as a polyaxial interlocking plate (Rimbus; Intercus GmbH; Rudolstadt, Germany) were used. Biomechanical testing consisted of a dynamic load sequence (preload 20 N, 1000 N up to 2500 N, stepwise increase of 100 N every 100 cycles, 0.5 mm/s) and a load to failure sequence (max. load 5000 N, 0.5 mm/s). Interfragmentary movement was detected via a 3-D optical measurement system. Boehler angle was measured after osteosynthesis and after failure occurred. Results: No significant difference regarding load to failure, stiffness, Boehler angle, or interfragmentary motion was found between the different fixation systems. A significant difference was found with the dynamic failure testing sequence where 87.5% of the Calcanail implants failed in contrast to 14% of the C-Nail group ( P < .01) and 66% of the Rimbus plate. The highest load to failure was observed for the C-Nail. Boehler angle showed physiologic range with all implants before and after the biomechanical tests. Conclusion: Both minimally invasive interlocking nail systems displayed a high primary stability that was not inferior to an interlocking plate. Clinical relevance: Based on our results, both interlocking nails appear to represent a viable option for treating displaced intra-articular calcaneal fractures.